Pengaruh Pemberian Blanket Warmer terhadap Hemodinamik pada Pasien Shivering Pasca Spinal Anestesi di IBS RSUD dr. Tjitrowardojo Purworejo - Adnan Khairuddin Hidayat; Muhaji Muhaji (Quantum Wellness : Jurnal Ilmu Kesehatan, 2025)
Surgery with spinal anesthesia techniques often causes complications such as hypothermia with shivering symptoms that can affect hemodynamics, one method of overcoming shivering is the provision of blanket warmers. Knowing the effect of blanked warmer on hemodynamics in shivering patients after spinal anesthesia in IBS RSUD dr.Tjitrowardojo Purworejo. This study used a type of quasi-experimental research with a pretest posttest control group design approach, sampling with purposive sampling. The research sample amounted to 30 respondents of post-spinal anesthesia patients. The results showed that there was an effect on hemodynamics as evidenced by the Wilcoxon Signed Rank Test in the experimental group of blood pressure P value 0.001 and pulse 0.000 in the control group obtained p value 1.000, and a different test using the mann whitney test obtained a significant value of blood pressure and pulse p value of 0.000 (α < 0.05). There is an effect of giving blanket waremer on hemodynamics in post-spinal anesthesia patients in IBS RSUD dr.Tjitrowardojo Purworejo. As an alternative and can improve the comfort of patients who experience hemodynamic disorders in postoperative shivering patients with spinal anesthesia.